2022
DOI: 10.17219/dmp/146195
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life (OHRQoL) in Polish adults with periodontal diseases, oral mucosal diseases and dental caries

Abstract: Background. With the development of medicine and extending the human lifespan, the next challenge for healthcare providers is to improve the quality of life. Oral Health Impact Profile (OHIP) is a worldwide known questionnaire that is used for assessing oral health-related quality of life (OHRQoL).Objectives. The aim of the present study was to assess the impact of periodontal diseases, oral mucosal lesions and dental caries on OHRQoL among Polish adults. Material and methods.A cross-sectional study consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…Oral lichen planus (OLP), and oral leukoplakia (OL) are forming a part of the OPMDs according to WHO classification [ 23 , 24 ]. Although the etiology and risk factors leading to the progression of most common OPMD – leukoplakia – into OSCC is smoking and chewing tobacco, for oral lichen planus as a the chronic T-cell-mediated autoimmune disease this search is still ongoing [ 25 , 26 ]. Among some of the factors named are the genetic background, type of dental materials used causing potential lichenoid reaction to it (as amalgam, metals, gold, and composite restorations) [ 25 , 27 ], drugs taken by the patient (i.e., cardiovascular agents, non-steroidal anti-inflammatory drugs, hypoglycemics) [ 27 , 28 ], and infectious agents like HSV and HPV [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral lichen planus (OLP), and oral leukoplakia (OL) are forming a part of the OPMDs according to WHO classification [ 23 , 24 ]. Although the etiology and risk factors leading to the progression of most common OPMD – leukoplakia – into OSCC is smoking and chewing tobacco, for oral lichen planus as a the chronic T-cell-mediated autoimmune disease this search is still ongoing [ 25 , 26 ]. Among some of the factors named are the genetic background, type of dental materials used causing potential lichenoid reaction to it (as amalgam, metals, gold, and composite restorations) [ 25 , 27 ], drugs taken by the patient (i.e., cardiovascular agents, non-steroidal anti-inflammatory drugs, hypoglycemics) [ 27 , 28 ], and infectious agents like HSV and HPV [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wigsten et al revealed that endodontic treatment improved oral healthrelated QoL (OHRQoL) more than tooth extraction one month following treatment [17]. OHRQoL is a multidimensional concept that describes the influence of the status of the oral cavity on the function, perceptions, and psychosocial well-being of an individual [18,19]. OHRQoL is an integral part of general health and well-being and is recognized by the World Health Organization as an important segment of the global oral health program [20].…”
Section: Introductionmentioning
confidence: 99%
“…Tools developed and validated for a specific population's age, local language, and diseases are required to accurately assess the OHRQoL. Several questionnaires have been developed in various languages, including the Geriatric Oral Health Assessment Index (GOHAI) and Oral Health Impact Profile (OHIP) [18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations